Frontispiece: Fluorescence‐Lifetime Imaging and Super‐Resolution Microscopies Shed Light on the Directed‐ and Self‐Assembly of Functional Porphyrins onto Carbon Nanotubes and Flat Surfaces. Issue 41 (21st July 2017) - Mao, Boyang; Calatayud, David G.; Mirabello, Vincenzo; Kuganathan, Navaratnarajah; Ge, Haobo; Jacobs, Robert M. J.; Shepherd, Ashley M.; Ribeiro Martins, José A.; Bernardino De La Serna, Jorge; Hodges, Benjamin J.; Botchway, Stanley W.; Pascu, Sofia I.
Abstract : Stimulated emission depletion ( STED) super‐resolution imaging and multiphoton fluorescence lifetime imaging techniques are used to image the aggregation of ZnII porphyrin arrays onto flat and conductive, as well as insulating, surfaces. New synthetic routes using directed‐ as well as self‐assembling methods of new, luminescent hybrids incorporating these functional porphyrins and pristine single‐walled carbon nanotubes (SWNTs) are reported. Multi‐domain imaging and spectroscopy techniques shed light on the potential implications of the covalent and supramolecular functionalization approaches in solution, dispersion, on surfaces and in the solid state. For more information, see the Full Paper by S. I. Pascu et al. onpage 9772 ff.